Regional Commuting in Italy: Do Temporary Contracts Affect the Decision? - Angela Parenti; Cristina Tealdi (European Regional Science Association (ERSA), 2015)
In this paper we study how the determinants of regional commuting in Italy have evolved in the past fifteen years. Using labour force data from 1992 to 2008 we estimate a model where the probability of commuting is regressed on a wide set of individual, job, firm and regional characteristics. Specifically, we focus on understanding how the increased exibility of the labour market in the late nineties/early twenties have affected the individual decision to commute across regions. Consistent with the previous literature, we identify specific types of individual working in firms with well-defined features who are more keen to commute. However, even though temporary employees tend to commute more than permanent employees, the increased utilization of temporary contracts did not have a strong impact on the commuting decisions of Italian workers.
Keywords: J41; J61; R23; 330; Commuting; Mobility; Regional studies; Labour market